Mapping of methionine-enkephalin-arg6-gly7-leu8 in the human diencephalon. (15th October 2016) - Sánchez, M.L.; Díaz-Cabiale, Z.; Narváez, J.A.; Manso, B.; Salinas, P.; Rivada, E.; Smith, V.; Coveñas, R.
Highlights: The chemical neuroanatomy of the pro-enkephalin system (Met-8-immunoreactivity) is reported in the human diencephalon. Six populations of cell bodies containing Met-8 were observed. Perikarya were mainly found in the hypothalamus. The lateral hypothalamic area showed the highest density of immunoreactive cell bodies. Peptidergic fibers were more widely distributed in the hypothalamus than in the thalamus. The density of the immunoreactive fibers observed in the diencephalic nuclei was low or moderate. Abstract: Using an immunohistochemical technique, we mapped the immunoreactive structures containing methionine-enkephalin-Arg 6 -Gly 7 -Leu 8 (Met-8) (a marker for the pro-enkephalin system) in the human diencephalon. Compared with previous studies, we observed a more widespread distribution of Met-8 in the human diencephalon. Met-8-immunoreactive cell bodies and fibers exhibited a more widespread distribution in the hypothalamus than in the thalamus. We observed six populations of Met-8-immunoreactive cell bodies. These perikarya were observed in the paratenial thalamic nucleus, ventromedial and dorsomedial hypothalamic nuclei, lateral hypothalamic area, pallidohypothalamic nucleus and in the paraventricular hypothalamic nucleus (posterior part). In the thalamus, Met-8-immunoreactive fibers were primarily observed in the midline region, whereas in the hypothalamus, these fibers were widely distributed. In general, a moderate/low density of Met-8-immunoreactive fibers was observed in the diencephalic nuclei. A moderate density was observed in the paraventricular thalamic nucleus, reuniens thalamic nucleus, lateral and medial geniculate nuclei, dorsomedial hypothalamic nucleus, paraventricular hypothalamic nucleus (posterior part) and ventromedial hypothalamic nucleus. The present study is the first to demonstrate the presence of clusters of Met-8-immunoreactive cell bodies in the human thalamus and hypothalamus, the distribution of fibers containing neuropeptides in the hypothalamus and the presence of these fibers in several thalamic nuclei. This neuroanatomical study will serve to elucidate the physiological roles of Met-8 in future studies of the human diencephalon.